Analysis of the relationship between governance mechanisms and performance indicators of business organizations - An Empirical Study in the Iraqi market for securities - حاكم محسن محمد (Iraqi Journal for Administrative Sciences, 2024)
is the mechanisms of governance controls ruler of conduct and ethics of business organizations and the goal is to walk the right path that connects these organizations to achieve their goals without deviations, reflecting that raised the performance of business organizations in a positive way if what has been the application of these controls tightly and comes research as a serious contribution on this road, as it underwent a series of private sector companies for research and study curriculum according to sound science and research concluded a set of conclusions and recommendations.